Nanopartículas metálicas: síntese em solventes eutéticos profundos e suas aplicações em eletroanalítica - Longatto, Gustavo Patelli (Universidade Federal de São Carlos, 2024)
In the field of nanotechnology, metallic nanoparticles stand out for their unique properties in relation to materials of similar composition but on micro or macrometric scales. Several studies have explored synthesis methods for these nanoparticles, highlighting electrodeposition, solvothermal methods and reaction with reducing agents or reagents in association with deep eutectic solvents. These eutectic solvents, known for their unique ability to dissolve compounds and an extensive range of compositions, offer a conducive environment for the synthesis of metal nanoparticles with manipulable/tunable properties. These nanomaterials have demonstrated significant usefulness in the development of electrochemical sensors, crucial in various applications, from medical diagnostics to the monitoring of environmental contaminants. Therefore, the present work aims to carry out a bibliographical review on the synthesis of metallic nanoparticles in deep eutectic solvents and explore their applications in the development of electrochemical sensors.
Metallic nanoparticles: synthesis in deep eutectic solvents and their applications in electroanalytical
Keywords: Nanotecnologia; Nanopartículas metálicas; Solventes eutéticos profundos (DES); Sensores eletroquímicos; Nanotechnology; Metallic nanoparticles; Deep eutectic solventes (DES); Electrochemical sensors; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA